A Frame-Based Analysis of Synaesthetic Metaphors - Wiebke Petersen; Jens Fleischhauer; Hakan Beseoglu; Peter Bücker (Baltic International Yearbook of Cognition, Logic and Communication, 2007)
The aim of this paper is to use a frame-based account to explain some empirical findings regarding the accessibility of synaesthetic metaphors. Therefore, some results of empirical studies will be discussed with regard to the question of how much it matters whether the concept of the source domain in a synaesthetic metaphor is a scalar or a quality concept. Furthermore, typed frames are introduced, and it is explained how the notion of a minimal upper attribute can be used in the analysis of adjective-noun compounds. Finally, frames are used to analyze synaesthetic metaphors; it turns out that they offer an adequate basis for the explanation of different accessibility rates found in empirical studies.
Keywords: philosophy; linguistics; communication